Design of water turbidity measurement using Arduino Uno R3 on the Martapura River - Mochammad Anshori; Nurma Sari; Amar Vijai Nasrulloh (Lambung Mangkurat University Press, 2022)
Water is a very important daily need in human life. Water is needed for drinking, preparing food, washing and cleaning. The water used must be suitable for use with quality according to physical, biological and chemical parameters. The aim of this study is to design an instrument for water turbidity which is a one of physical parameter. Turbidity occurs due to the scattering of particles that affect the absorption of light rays in water, such as sediment. Feasible water has a turbidity value of 25 NTU. The tool for measuring water turbidity uses a turbidity sensor SKU: SEN0189 which has been integrated with the Arduino Uno R3 microcontroller and can store measurement results automatically through the Delphi 7.0 interface software in .xls format. This water turbidity measuring instrument can be applied with a smart water tool, so that the percentage value of the decrease in the level of turbidity of water that has been carried out by the filtration process can be known. The test results of the water turbidity measuring instrument showed that turbidity ≤452 NTU had a standard deviation value of ±2 NTU and turbidity ≥520 NTU had a standard deviation value of ±1. The implementation of a river water turbidity measuring instrument using a SKU:SEN0189 turbidity sensor has been carried out in Martapura river water with 3 different location points. The measurement results before filtration show that the highest turbidity value is 124 NTU at point 1, 130 NTU at point 2, and 189 NTU at point 3. In the measurement after filtration, the smallest turbidity value is 9 NTU at point 1, 9 NTU at point 2, and 13 NTU at point 3. This shows that after the filtration process of Martapura river water has been carried out with a smart water tool, Martapura river water can be used for sanitary hygiene purposes according to the water turbidity parameter with a value below the 25 NTU threshold.